Help-seeking behavior among community-dwelling adults with chronic pain. Issue 1 (1st January 2019) - Mann, Elizabeth G.; VanDenKerkhof, Elizabeth G.; Johnson, Ana; Gilron, Ian
ABSTRACT: Background: Some individuals with chronic pain do not seek care. This decision may be due to characteristics of the individual, pain, and/or their health professional(s). Aims: This study aimed to identify and compare features of individuals with chronic pain, their pain and general health, and their health care professional between community-dwelling adults who did and did not seek care. Methods: Randomly selected adults were mailed a study questionnaire that screened for chronic pain (pain persisting ≥3 months) and asked about their general well-being (Short Form [SF]-36), pain location (body diagram), pain intensity and characteristics (Leeds Assessment of Neuropathic Symptoms and Signs), experiences with health care professionals (Chronic Illness Resources Survey), and visits made to health professionals over the past year. Respondents were categorized as help-seeking (≥1 visit in the past year) and non-help-seeking (zero visits in the past year). Results: Six percent of respondents (44/696) were non-help-seeking. These respondents differed in individual, pain, and health care professional characteristics when compared to those who did seek care. Specifically, when other variables were controlled, non-help-seeking individuals were less likely to be male (relative risk [RR] = 0.39, 95% confidence interval [CI], 0.18–0.86), report comorbid conditions (RR = 0.46, 95% CI, 0.22–0.98), report being treated as an equal partner in decision making (RR = 0.40, 95% CI, 0.18–0.93), and rate their health care professional as important to their pain management (RR = 0.39, 95% CI, 0.18–0.85). They were more likely to use over-the-counter medication to manage their pain (RR = 2.52, 95% CI, 1.14–5.58). Conclusions: Experiences with health professionals play a role in determining whether an individual manages his or her pain independently. Future research should explore the safety of those who do not seek care.